2012
DOI: 10.1152/ajpcell.00196.2011
|View full text |Cite
|
Sign up to set email alerts
|

Effects of low glucose on carotid body chemoreceptor cell activity studied in cultures of intact organs and in dissociated cells

Abstract: The participation of the carotid body (CB) in glucose homeostasis and evidence obtained in simplified cultured CB slices or dissociated cells have led to the proposal that CB chemoreceptor cells are glucoreceptors. However, data generated in intact, freshly excised organs deny CB chemoreceptor cells' glucosensing properties. The physiological significance of the contention has prompted the present study, performed in a newly developed preparation of the intact CB organ in culture that maintains chemoreceptor c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
1
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 57 publications
3
33
1
4
Order By: Relevance
“…The responsiveness of mammalian CB cells to hypoglycemia has been confi rmed in the in vitro CB-petrosal ganglion preparation (Zhang et al 2007 ) and in dispersed cat glomus cells (Fitzgerald et al 2009 ). Nonetheless, other authors have failed to fi nd any responsiveness of explanted whole CB preparations to low glucose (Bin-Jaliah et al 2004 ;Conde et al 2007 ) or any signifi cant changes in cytosolic [Ca 2+ ] in dispersed glomus cells in response to rapid glucose removal (Gallego-Martin et al 2012 ). In contrast to these last observations, we have found that, as in the rat (Garcia-Fernandez et al 2007 ), human glomus cells can also depolarize and release transmitters in response to a decrease in the extracellular glucose concentration (Ortega-Saenz et al 2013 ).…”
Section: Cellular Responses To Hypoglycemiacontrasting
confidence: 84%
“…The responsiveness of mammalian CB cells to hypoglycemia has been confi rmed in the in vitro CB-petrosal ganglion preparation (Zhang et al 2007 ) and in dispersed cat glomus cells (Fitzgerald et al 2009 ). Nonetheless, other authors have failed to fi nd any responsiveness of explanted whole CB preparations to low glucose (Bin-Jaliah et al 2004 ;Conde et al 2007 ) or any signifi cant changes in cytosolic [Ca 2+ ] in dispersed glomus cells in response to rapid glucose removal (Gallego-Martin et al 2012 ). In contrast to these last observations, we have found that, as in the rat (Garcia-Fernandez et al 2007 ), human glomus cells can also depolarize and release transmitters in response to a decrease in the extracellular glucose concentration (Ortega-Saenz et al 2013 ).…”
Section: Cellular Responses To Hypoglycemiacontrasting
confidence: 84%
“…TASK does not appear to be involved, as TASK activity is unchanged during such transient depolarizations. Presence of spontaneous oscillation in [Ca 2+ ] i has also been reported earlier [28]. Because glomus cells in the carotid body are believed to be electrically-coupled by gap junctions [2], it is possible that spontaneous [Ca 2+ ] i oscillations occur under normoxic conditions for all glomus cells in vivo, but not in dispersed cells.…”
Section: Relative Roles Of Task and Bk In Stimulus-secretion Couplingsupporting
confidence: 62%
“…This result is consistent with other acute studies (Bin-Jaliah et al 2004; Conde et al 2007). Although cultured models show glucose sensitivity of glomus cells (Pardal and López-Barneo 2002; Zhang et al 2007), phenotypic changes in glucose sensitivity during culture has been indicated (Gallego-Martin et al 2012). Collectively, it seems that the carotid body, if not cultured, does not sense glucose levels directly.…”
Section: 4 Discussionmentioning
confidence: 99%
“…Chemoreceptor discharge was not increased with low glucose (Bin-Jaliah et al 2004; Conde et al 2007), although the effect of cyanide on chemoreceptor discharge was enhanced by low glucose (Alvarez-Buylla and Alvarez-Buylla 1988). Moreover, phenotypic changes of glomus cells during culture have been suggested (Gallego-Martin et al 2012). Nevertheless, several experimental data suggest that the carotid body is involved in whole body glucose metabolism: experimentally induced perturbation of glucose metabolism was blocked by carotid body afferent denervation (Alvarez-Buylla and Alvarez-Buylla 1988; Koyama et al 2000; Shin et al 2014; Wehrwein et al 2010).…”
Section: 1 Introductionmentioning
confidence: 99%